Using Information Communication Technology to Expedite Citizen Monitoring for Public Sector Transparency in Nigeria: The Case of Tracka – a BudgIT initiative - Ogunjobi, Olabanji (KDI School of Public Policy and Management, Global Delivery Initiative, 2020)
This case study examines how BudgIT, a civic organization focused using technology for citizen engagement in Nigeria, worked to enable effective citizen monitoring of Nigeria’s public budgets, and ultimately to ensure that these budgets were effective in addressing citizens’ needs. Nigerian society faced significant challenges related to combating corruption, fostering transparency, and catalyzing civic engagement. With regard to budgets, most citizens were not very motivated to demand transparency from public officials, due to limited understanding of public finances. To address this challenge, BudgIT launched an initiative to democratize budget information and to help citizens across all literacy spans understand better the content of the national budget, especially about capital projects implementation in their respective communities. It later developed Tracka, a citizen-led project tracking initiative to enable citizens to hold government officials to account. Using creative technology, tracking officers, alliances with other civil society organizations, and community engagement, BudgIT overcame a number of delivery challenges and institutional traps to bolster Nigerians’ engagement with public budgets and enable greater accountability.
Keywords: Increasing budget transparency; Stakeholder engagement; Organizational capacity